2003
DOI: 10.1227/01.neu.0000093199.74960.ff
|View full text |Cite
|
Sign up to set email alerts
|

Poor-grade Aneurysmal Subarachnoid Hemorrhage: Outcome after Treatment with Urgent Surgery

Abstract: The high ultraearly rebleeding rate indicates a need to urgently secure the ruptured aneurysm by performing surgery or coiling, and this indication is more pronounced for poor-grade patients than for good-grade patients. The outcome results of ultraearly surgery indicate that a nonselective policy does not lead to a large number of dependent survivors, even among elderly poor-grade patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 26 publications
7
75
3
3
Order By: Relevance
“…However, the majority of patients would succumb to rebleeding and cerebral vasospasm prior to surgery (1)(2)(3). Recent studies have suggested that ultra-early microsurgery within 24 h of SAH may improve the prognosis of patients with poor-grade aneurysm, since it may prevent rebleeding and may delay the release of toxic substances during cerebral vasospasm, thus reducing damage to the brain (15)(16)(17)(18). It was previously considered that early surgery or delayed surgery was meaningless to improve the prognosis of patients with poor-grade aneurysm following SAH (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the majority of patients would succumb to rebleeding and cerebral vasospasm prior to surgery (1)(2)(3). Recent studies have suggested that ultra-early microsurgery within 24 h of SAH may improve the prognosis of patients with poor-grade aneurysm, since it may prevent rebleeding and may delay the release of toxic substances during cerebral vasospasm, thus reducing damage to the brain (15)(16)(17)(18). It was previously considered that early surgery or delayed surgery was meaningless to improve the prognosis of patients with poor-grade aneurysm following SAH (4).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to solve the problem by simple microsurgical clipping and endovascular coiling. Certain authors prefer to use endovascular coiling, since it is considered to present several advantages, including less trauma and shorter preoperative preparation or operative time when compared to general surgery (17). However, this procedure is generally ineffective or even aggravating for removing the intracranial hematoma and resolving the vasospasm (24,25).…”
Section: A B C D Ementioning
confidence: 99%
See 1 more Smart Citation
“…Some smaller scale single-center studies suggested that early surgical clipping may lead to better results, but mostly in selected groups. 3,13,14 A study that included patients with poor-grade SAH who did not receive aneurysm treatment (ie, neither clipping nor coiling) reported a mortality rate of 71%. 15 Specifically lacking from the endovascular studies are data analogous to the evidence base for early clipping, which compares coiling with conservative treatment; and the argument largely depends on the extrapolated assumption that coiling is a benign intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the prospective Cooperative Aneurysm Study [50], the rate of rebleeding was 4% on the first day after SAH and then constant at a rate of 1% per day to 2% per day over the following 4 weeks. Recent studies found that all preoperative rebleeding occurred within 12 hours of initial SAH and 70% of ultraearly rebleeds occurred within 2 hours of initial SAH [51,52].A large retrospective study reported a rebleeding rate of 6.9% after admission but no relationship to blood pressure [53].…”
Section: Rebleedingmentioning
confidence: 99%